Human Neural Stem Cell Transplantation Rescues Cognitive Defects in APP/PS1 Model of Alzheimer’s Disease by Enhancing Neuronal Connectivity and Metabolic Activity - Li, Xueyuan; Zhu, Hua; Sun, Xicai; Zuo, Fuxing; Lei, Jianfeng; Wang, Zhanjing; Bao, Xinjie; Wang, Renzhi (Frontiers in Aging Neuroscience, 2016)
Alzheimer’s disease (AD), the most frequent type of dementia, is featured by Aβ pathology, neural degeneration and cognitive decline. To date, there is no cure for this disease. Neural stem cell (NSC) transplantation provides new promise for treating AD. Many studies report that intra-hippocampal transplantation of murine NSCs improved cognition in rodents with AD by alleviating neurodegeneration via neuronal complement or replacement. However, few reports examined the potential of human NSC transplantation for AD. In this study, we implanted human brain-derived NSCs (hNSCs) into bilateral hippocampus of an APP/PS1 transgenic mouse model of AD to test the effects of hNSC transplantation on Alzheimer’s behavior and neuropathology. Six weeks later, transplanted hNSCs engrafted into the brains of AD mice, migrated dispersedly in broad brain regions, and some of them differentiated into neural cell types of central nervous system. The hNSC transplantation restored the recognition, learning and memory deficits but not anxiety tasks in AD mice. Although Aβ plaques were not significantly reduced, the neuronal, synaptic and nerve fiber density was significantly increased in the frontal cortex and hippocampus of hNSC-treated AD mice, suggesting of improved neuronal connectivity in AD brains after hNSC transplantation. Ultrastructural analysis confirmed that synapses and nerve fibers maintained relatively well-structured shapes in these mice. Furthermore, in-vivo magnetic resonance spectroscopy showed that hNSC-treated mice had notably increased levels of NAA and Glu in the frontal cortex and hippocampus, suggesting that neuronal metabolic activity was improved in AD brains after hNSC transplantation. These results suggest that transplanted hNSCs rescued Alzheimer’s cognition by enhancing neuronal connectivity and metabolic activity through a compensation mechanism in APP/PS1 mice. This study provides preclinical evidence that hNSC transplantation can be a possible and feasible strategy for treating patients with AD.